Acceptance and Commitment Therapy for Mild Traumatic Brain Injury (ACTion-mTBI): A Quasiexperimental Feasibility Study. - Faulkner, Josh; Prouty, Devin; Devlin, Lucy; Appleton, Damien; Roche, Maree; Below, Karen; Moffat, John; Snell, Deborah; Williams, Matt N; Barker-Collo, Suzanne; Theadom, Alice (BMJ, 2025)
OBJECTIVES: This study aimed to determine the feasibility of recruiting, implementing and delivering an acceptance and commitment therapy (ACT) intervention for mild traumatic brain injury (mTBI) (ACTion-mTBI) within a multidisciplinary outpatient mTBI rehabilitation services. The study also aimed to conduct a preliminary investigation of group differences between ACTion-mTBI and an equivalent cognitive behavioural therapy (CBT) intervention on various outcome measures and psychological treatment targets. DESIGN: A two-arm quasiexperimental feasibility study. SETTING: Five mTBI rehabilitation clinics throughout New Zealand. INTERVENTION: Psychologists working in mTBI rehabilitation clinics throughout New Zealand were trained to deliver ACTion-mTBI or CBT. Eligible participants were assigned to either of these interventions based on the psychologist available at the clinic they were referred to. ACTion-mTBI is a five sessions intervention that incorporates all six components of the ACT model. The CBT intervention is an equivalent intervention and incorporating all four components of the CBT model. Both interventions are adapted for an mTBI context. PRIMARY OUTCOME MEASURES: The primary outcomes were related to the feasibility of ACTion-mTBI. This included recruitment, retention and treatment adherence of participants, study procedure and fidelity of treatment delivery. SECONDARY OUTCOME MEASURES: To explore group differences between ACTion-mTBI and CBT on functional disability, postconcussion symptoms, mental health, valued living and psychological flexibility. RESULTS: The intervention proved feasible to implement with community-based mTBI rehabilitation services. Attrition rates were comparable between the two psychological interventions and fidelity to the treatments was high. At post-treatment, when covarying pretreatment scores, ACTion-mTBI had a significantly greater improvement in functional disability than CBT (moderate effect). ACTion-mTBI also had a significantly greater reduction in postconcussion symptoms, anxiety and stress. Promisingly, significant improvements in psychological flexibility was also found post-treatment. There were no group differences on depressive symptoms and valued living. CONCLUSION: We conclude that a full clinical trial of ACTion-mTBI for individuals with mTBI is feasible and warranted. TRIAL REGISTRATION NUMBER: ACTRN1262100059482.
Keywords: Brain Injuries; Feasibility Studies; Psychosocial Intervention; 4201 Allied Health and Rehabilitation Science; 5203 Clinical and Health Psychology; 42 Health Sciences; 52 Psychology; Mind and Body; Mental Illness; Neurosciences; Traumatic Head and Spine Injury; Physical Injury - Accidents and Adverse Effects; Behavioral and Social Science; Clinical Trials and Supportive Activities; Brain Disorders; Rehabilitation; Mental Health; Clinical Research; Depression; 6.6 Psychological and behavioural; 5.6 Psychological and behavioural; Mental health; 3 Good Health and Well Being; 1103 Clinical Sciences; 1117 Public Health and Health Services; 1199 Other Medical and Health Sciences; 32 Biomedical and clinical sciences; 42 Health sciences; 52 Psychology; Humans; Feasibility Studies; Adult; Female; Male; Acceptance and Commitment Therapy; New Zealand; Brain Concussion; Middle Aged; Cognitive Behavioral Therapy; Young Adult; Treatment Outcome; Humans; Feasibility Studies; Adult; Female; Male; Acceptance and Commitment Therapy; New Zealand; Brain Concussion; Middle Aged; Cognitive Behavioral Therapy; Young Adult; Treatment Outcome